Epidemiologic characteristics of COVID-19 infection in the Republic of Srpska: a hundred days survey - Aćimović, Jela; Jandrić, Ljubica; Đaković Dević, Jelena; Subotić, Branka; Radojčić, Tina; Bojanić, Janja; Rodić Vukmir, Nina; Zeljković, Branislav (Scripta Medica, 2020)
Background/Aim: The World Health Organization (WHO) declared the spread of a novel disease COVID-19 as a pandemic on 11 March 2020. As of 12 June, there have been more than 7.4 million COVID-19 cases and more than 418,000 COVID-19 deaths globally. This paper represents epidemiological analysis of the first 100 days of COVID-19 epidemic in the Republic of Srpska. Methods: Data of all COVID-19 cases confirmed in the Republic of Srpska between 4 March and 12 June were collected from epidemiological and laboratory testing reports obtained from the Public Health Institute of the Republic of Srpska. This cross-sectional analysis was carried out on a sample of 1,607 laboratory-confirmed COVID-19 cases, which included: summary of patient characteristics, examination of age distributions and sex ratios, calculation of case fatality and mortality rates, incidence rates analysis, epidemiological curve construction and subgroup analysis. Results: Over 100 days after the first case was confirmed, the total number of infected patients in the Republic of Srpska rose to 1,607 (31,471 persons had been tested). As of 12 June, 69.9 % of those cases has recovered. During that period there were 117 confirmed deaths (average age 72 years; 60.7 % males; 86 % older than 60 years; 94 % with at least one comorbidity). The sex ratio among the confirmed cases was 0.95:1 (48.7 % men vs 51.3 % women). Infections were less common in persons below 20 years of age (7.3 % of all confirmed cases) and the majority of the affected persons were in the group 40-69 years of age. As much as 86 % of all death cases occurred in persons older than 60 years (average age 72 years) and 94 % of all death cases had at least one underlying condition (mostly cardiovascular diseases, 79.5 %). Conclusion: Evaluating the clinical data of COVID-19 patients, finding the source of infection and studying the behavior of the disease is crucial for understanding of the pandemic.